2(x+1)-5=3(x-2)

Simple and best practice solution for 2(x+1)-5=3(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+1)-5=3(x-2) equation:


Simplifying
2(x + 1) + -5 = 3(x + -2)

Reorder the terms:
2(1 + x) + -5 = 3(x + -2)
(1 * 2 + x * 2) + -5 = 3(x + -2)
(2 + 2x) + -5 = 3(x + -2)

Reorder the terms:
2 + -5 + 2x = 3(x + -2)

Combine like terms: 2 + -5 = -3
-3 + 2x = 3(x + -2)

Reorder the terms:
-3 + 2x = 3(-2 + x)
-3 + 2x = (-2 * 3 + x * 3)
-3 + 2x = (-6 + 3x)

Solving
-3 + 2x = -6 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-3 + 2x + -3x = -6 + 3x + -3x

Combine like terms: 2x + -3x = -1x
-3 + -1x = -6 + 3x + -3x

Combine like terms: 3x + -3x = 0
-3 + -1x = -6 + 0
-3 + -1x = -6

Add '3' to each side of the equation.
-3 + 3 + -1x = -6 + 3

Combine like terms: -3 + 3 = 0
0 + -1x = -6 + 3
-1x = -6 + 3

Combine like terms: -6 + 3 = -3
-1x = -3

Divide each side by '-1'.
x = 3

Simplifying
x = 3

See similar equations:

| 18a+14b+4c+4c-4b-6a= | | 18a+16b+4c+4c-4b-6a= | | 3x+7+x-4-2x+1=8 | | (7/11)^11 | | 4/10+3/9 | | -2(x-3y)= | | (8x^4y^9z^3)(3xz^7)= | | 10-(8x-2)=-8x-3 | | (3x^9)(2x^3)= | | -2x+6=4x | | 37-x+9x-27=180 | | 3(5c+3)-28=11c+1 | | -x-4=-15 | | (3x^8)(-6)= | | 5x+6=126 | | 3a-3=-11 | | 3-2x=12+7x | | 4a(3a-5b)= | | 5x^2+29-6= | | 5x-y=24 | | -6/7x+15=-33 | | 26x+21=32x-9 | | 3x^2+10x=32 | | 1/9y=-7 | | -4(y-9)=-10(2-y) | | x=4x+2 | | z-1/2=-1/4 | | .3x-4.2=2.4 | | .3-4.2=2.4 | | 60-2x=30 | | 12/18 | | 6-66.6666666667x=-8 |

Equations solver categories